Simulation Modelling for Lean Production: Case Study - Wan Mahmood, W.H.; Yusup, M.Z.; Salleh, M.R.; Muhamad, M.R.; Ab Rahman, M.N. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This article presents the simulation results of using Arena software in investigating the influence of lean production that depend on sequencing techniques in a manufacturing firm which operates based on engineer-to-order. By using the actual data collected from a case study, two sequencing techniques, Johnson Rule’s and Critical Ratio were applied. The result showed that the use of sequencing techniques in an engineer-to-order operation was beneficial in optimising the operating time, and increasing output number. The finding will benefit manufacturing firms in making strategic decision to implement lean production in engineer-to-order operations.